Peran PT Sirtu Karya Utama Dalam Meningkatkan Kesejahteraan Masyarakat Di Kelurahan Buluri - Nurfitriani, Nurfitriani (Journal of Principles Management and Business, 2022)
With the mining company C PT. Sirtukarya Utama has an impact on the welfare of the people of Buluri Village. Based on this, the researcher is interested in raising this issue in the form of a thesis with the title "The Impact of the Existence of Quarrying Company C PT. Main Situkarya in Improving Community Welfare in Buluri Sub-district”. The research method used is using a qualitative descriptive approach, through primary data sources and secondary data, using observation, interviews, and documentation as data collection techniques. The results of the study show that: The impact of the mining company C PT. Main Sirtukarya to the Buluri Village community, namely: 1). Income, creating jobs. 2). Housing, people can build permanent houses. 3). Education, people can send their children to a higher level. 4). Health, people can meet the protein intake needed by the body. Meanwhile, the impact of Galian C PT. Main Sirtukarya Islamic economic perspective, namely: 1). Please Help, PT Sirtukarya Utama provides jobs so that people can meet their daily needs. 2). Responsibility, the company does not cause damage to nature and ecosystems in the Buluri sub-district. 3). Fair, companies provide salaries in accordance with the field or job.